Russian Cultural Scripts: The Theory of Cultural Scripts and Its Applications - Wierzbicka, Anna (Ethos (Berkeley, Calif.), 2002)
"Cultural scripts" as understood in this article are representations of cultural norms that are widely held in a given society and that are reflected in language (in culture-specific "keywords," phrases, conversational routines, and so on). A key methodological principle in the theory underlying this article is that the proposed cultural scripts must be formulated in the Natural Semantic Metalanguage, that is, in terms of empirically established universal human concepts, encoded in words that have exact semantic equivalents in all languages. As D'Andrade notes, the Natural Semantic Metalanguage "offers a potential means to ground all complex concepts in ordinary language and translate concepts from one language to another without loss or distortion in meaning" (2001:246). What applies to concepts applies to shared understandings, that is, to what the author and colleagues have been calling, for more than a decade, "cultural scripts." The author argues that "cultural scripts" formulated in universal human concepts allow us to understand cultural norms and attitudes from within, that is, from the point of view of the "actors," while at the same time making them intelligible to outsiders. In this article, the theory of cultural scripts is applied to Russian culture and, in particular, the Russian cultural scripts concerning speech, truth, and interpersonal communication ("obščenie").